Pengaruh Pasca-Pemrosesan Annealing Terhadap Sifat Mekanis Polimer Hasil Cetak 3D Fused Deposition Modeling (FDM) - Pratama, Juan (Jurnal Sains & Teknologi Fakultas Teknik Universitas Darma Persada, 2023)
Nowadays, 3-dimensional (3D) printing technology using the Fused Deposition Modeling (FDM) type for processing polymer materials is widely known and used because of its capability to produce products with complex shapes. Even though they have many advantages, FDM 3D printed products also have several disadvantages, where low mechanical properties are one of the main weaknesses of FDM 3D printed products caused by the non-uniform cooling process in the FDM 3D printed polymer material. In this research, post-processing annealing was carried out to determine the effect of reheating and uniform cooling on the mechanical properties of polylactic acid (PLA) 3D printed FDM results. The specimens were printed by varying the raster angle in the print parameters. Then, 3 variations of annealing temperature were used, i.e., 80, 120, and 150 °C. The research results show that post-processing annealing does not have a significant effect on the tensile strength, elongation, and elastic modulus of 3D FDM printed PLA, regardless of the raster angle used. In the end, this research can confirm one of the previous findings that post-processing annealing is a less effective method for improving the mechanical properties of FDM 3D printed products, especially PLA.